Isolation and Identification of Airborne Bacteria Inside Swiftlet Houses in Sarawak, Malaysia - Sien, Leong Sui; Chuan, Chia Hwa; Lihan, Samuel; Yee, Ling Teck (Makara Journal of Science, 2013)
Air consists of such microorganisms as bacteria, fungi, and viruses. Exposure to these airborne bacteria indoors may cause infectious and noninfectious adverse health effects. However, the sources and origins of bacteria are not fully understood. The aim of this study was to isolate and identify the bacteria present in the air inside swiftlet houses located in Kota Samarahan, Saratok, Betong, Maludam, Miri, Kuching, Semarang, Sepinang, Sarikei, and Sibu in Sarawak, Malaysia. A total of 100 bacterial isolates from 20 samples were collected from swiftlet houses. The bacteria present in the air were collected using Plate Count Agar. Two plates were exposed at the front and back inside swiftlet houses for 15 sec and then incubated at 37 ± 1 oC for 24 h. The 16S rRNA analysis method was used to identify the isolates from the samples. The air inside the swiftlet houses had a total mean airborne bacteria colony count of 2.02 ± 0.72 log10 cfu/m2 /sec; the highest was in Miri (3.08 ± 0.29 log10 cfu/m2 /sec), and the lowest was in Sibu (1.05 ± 0.85 log10 cfu/m2 /sec). Twenty-seven bacteria species were identified, and Lysinibacillus sp. B4 (16%) was most frequently isolated